Preliminary analysis of the melanoma multimedia educational program for general practitioners on behalf of the Italian melanoma intergroup - Federica Zamagni; Fabio Falcini; Serena Magi; Lauro Bucchi; Silvia Mancini; Rosa Vattiato; Emanuele Crocetti; Stefano Falcinelli; Claudio Feliciani; Maurizio Lombardo; Davide Melandri; Maria Antonietta Pizzichetta; et al. (PAGEPress Publications, 2024)
Introduction. According to the National Oncological Plan 2023-2027 on the importance of multidisciplinary and interactive e-learning training, the Italian Melanoma Intergroup (IMI) has developed MelaMEd (Melanoma Multimedia Education), a national project for general practitioners (GPs) on the prevention and detection of cutaneous melanoma through an online platform and an online course. MelaMEd enables participants to (1) recognize skin lesions that require specialist dermatological assessment, (2) select patients at high risk of melanoma and (3) be informed of the diagnosis and treatment pathway of patients with melanoma. Methods. A free online platform and online course were developed and launched in June 2022. Before starting the course, enrolled participants fill out a pre-training questionnaire concerning the basic knowledge of the disease and the recognition and management of suspicious lesions. After the course, participants will fill out the same questionnaire again. The online course will end in December 2023. Here we present a preliminary analysis of the pre-training results (January 2023-July 2023). The data have been analyzed descriptively. Results. So far, five healthcare centers have participated in the project for a total of 1320 participants. Of these, 298 compiled the pre-training questionnaire. Forty-seven percent of them were aged <40 years. Respondents were almost divided between GPs (47%) and resident GPs (48%). Among the theoretical questions, the "ABCDE" rule and "ugly duckling" sign are well known (96% and 91% of correct answers, respectively), but a lower percentage (68%) of respondents knows the "EFG" rule for the recognition of nodular melanomas and the statement of Breslow thickness (29%). Regarding the series of clinical images of pigmented skin lesions and their management, the percentages rate of accuracy varied from 33% to 87%: melanoma (5 cases) ranges from 36% to 71%, melanocytic nevi (3 cases) from 33% to 84%, whereas the percentages rate of referral for dermatological evaluation varied from 44% to 99%. Melanoma cases referred to dermatologist ranges from 67% to 99%. Conclusions. This preliminary analysis on pre-training questionnaire mainly showed a lack of knowledge of the two major points of melanoma diagnosis (EFG) and management (Breslow thickness), as well as a low rate of participants. We will compare the proportions of correct answers to the questionnaires before and after the course once available.